PENGARUH KESADARAN WAJIB PAJAK, PENGETAHUAN PAJAK, DAN AKUNTABILITAS PELAYANAN PUBLIK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR (Studi Kasus Kantor UPTB SAMSAT Kabupaten Muna) - Aswati, Waode; Nudi, Tuti Nurdianti (JURNAL AKUNTANSI DAN KEUANGAN, 2018)
ABSTRACTThis study aims to determine the effect of taxpayer awareness, tax knowledge, and accountability of public services to taxpayer compliance in paying motor vehicle tax at UPTB Samsat Muna Regency. This study uses primary data as much as 99 samples with the method of determiningaccidental sampling samples. Data collection is done through interview method, koesioner, and literature study. Data analisys technique used is multiple linear regression analisys.The results of this study indicate that taxpayer awareness variable. And tax knowledge partially have a positive and significant impact on taxpayer compliance, an accountability of public services partially negatively and not significant effect on compliance of motor vehicle taxpayer in UPTB Samsat Muna Regency. While the simultaneous variable of taxpayer awareness, tax knowledge, and accountability of public services have a positive and significant impact on tax payer compliance in paying motor vehicle tax at UPTB samsat Muna Regency. Â Keywords: awareness, knowledge, public service accountability, compliance, taxÂ